Oxygen Saturation Diagnostic Accuracy Against COVID-19 in Rural Areas of Indonesia (Majalah Kedokteran Bandung, 2023)
As a country with a high proportion of rural areas, Indonesia continues to struggle with a rapid and accurate diagnosis of COVID-19, necessitating the development of a diagnostic tool or parameter that is less expensive, easier to obtain, and produces rapid results. This retrospective study aimed to explore the diagnostic accuracy of oxygen saturation in detecting COVID-19 in rural areas of Indonesia. Data were collected consecutively  from medical records of adult patient (30 – 90 years old) suspected of having COVID-19 based on the WHO criteria and  underwent RT-PCR swab test in three (3) hospitals in one of the regions of Indonesia during the timeframe of May 1, 2020 to September 31, 2021. Analysis was conducted using the cross-table analysis with sensitivity, specificity, positive predictive value, negative predictive value, and area under the curve (AUC) as the variables with their respective confidence interval. Results indicated that 548 of 700 patients included in the analysis were confirmed positive for COVID-19 based on the RT-PCR test results. The sensitivity, specificity, positive predictive value, negative predictive value, and area under the curve (AUC) value of oxygen saturation for detecting COVID-19 were 33% (CI 95% 29 – 37%), 78% (CI 95% 72 – 85) %), 84% (CI 95% 80 – 89%), 24% (CI 95% 21 – 28%), and 56% (CI 95% 51– 61%), respectively.  Thus,  the oxygen saturation level alone does not have adequate diagnostic accuracy for the diagnosis of COVID-19 and, therefore, is not recommended to be used for diagnosing COVID-19.
Keywords: COVID-19; Indonesia; Oxygen Saturation